The Effects of Weekly Response Related to the Number of Training Sessions on Psychological Factors and Memory of Sedentary Elderly - Farnaz Torabi; Abolfazl Farahani; Ali Arbabi (University of Tehran, 2017)
The aim of the present study was to determine the effects of the number of training sessions in a week on psychological factors and memory of sedentary elderly. For this purpose, 45 sedentary male elderly (mean age, 73.15±6.54 years; height, 166.5±3.10 cm; weight, 64.45±4.06 kg; body mass index (BMI), 23.49±1.51 kg/m2) were voluntarily selected and divided into two training groups and one control group with their own desire. The 8-week training program in two-session group consisted of running with intensity of 40-55% of maximum heart rate for 2 sessions a week. Subjects in four-session group used a training program with similar intensity of two-session group for 4 sessions a week. Depression, anxiety, happiness and memory status were measured using the Beck Depression, Beck Anxiety, Oxford Happiness and Wechsler Memory tests. Data were analyzed using paired t test and one-way ANOVA (P<0.05). The results showed a significant improvement in psychological factors and memory in experimental groups compared with the control group (P<0.05). Subjects who had practiced four sessions a week showed more improvement in depression, anxiety, happiness and some memory factors. Generally, both training programs had useful adaptation and increased number of training sessions has more influence in the improvement of psychological factors and memory in the elderly.